Pengaruh Media E-Comic Berbasis Aplikasi Canva Terhadap Pemahaman Nilai-Nilai Pancasila Pada Siswa Kelas IV - Risnovia, Nurdyta; Tarmizi, Pebrian; Susanti, Atika (JURIDIKDAS, 2025)
This study aims to determine the Effect Of E-comic Media Based On Canva Application On Understanding The Values Of Pancasila In Grade IV Students Of SD Negeri Cluster X Bengkulu City. This research is a type of quantitative research. The research method used is a quasi experimental method with the research design The Matching Only Pretest-Posttest Control Group Design. The population in this study were fourth grade elementary school students of Gugus X Bengkulu City. The research sample was taken using the Cluster Random Sampling technique, resulting in grade VI of State Elementary School 58 Bengkulu City as the experimental class and grade IV of State Elementary School 15 Bengkulu City as the control class. The instrument used was a written test sheet in the form of multiple choice questions totaling ten items with data collection techniques in the form of pretest and posttest. Based on the results of the t-test calculation, the student posttest score obtained a sig. (2- tailed). This shows that there is a difference in posttest results between the experimental class and the control class due to the treatment of the two different classes. Thus, it can be concluded that there is an effect of e-comic media based on canva application on understanding the values of Pancasila in grade IV students of SD Negeri cluster X Bengkulu City.